Incorporation of homogenous ceramic tile waste to enhance mechanical properties of mortar - Mohd Sam, A.; Samadi, M.; Hussin, M.; Lee, H.; Ismail, Mohamed; Abdul Shukor Lim, N.; Ariffin, N.; Khalid, N.; Abd Majid, M.; Mirza, J. (2015)
© 2015 Penerbit UTM Press. All rights reserved. Reduction, reuse and recycle of industrial and agricultural waste materials are regarded as very important to provide sustainable construction. The by-products such as fly ash, silica fume, slag and palm oil fuel ash, etc., have been studied for the past few decades and the findings are very well accepted as new innovative materials in construction. Currently, ceramic materials are widely used in many parts of the world. Consequently a large quantities of wastes are produced simultaneously by brick and tile manufacturers and from construction industry. Most of these wastes are dumped in landfills that cause environmental problem. In the present research the effect of homogeneous ceramic tile waste as sand replacement was investigated on the harden properties of mortar. The tests conducted under laboratory ambient condition were compressive and splitting tensile strengths. The percentage replacement of sand by ceramic aggregate by weight was in the range of 0% to 100%. The size of ceramic aggregate used is modified in accordance to ASTM C33-13. All samples were cast in a 50mm cube and cured in water until the age of testing. The results showed that the compressive strength values of the control sample and 100% ceramic aggregate as sand replacement at the age of 7days were 41.9 MPa and 40.9 MPa, respectively; almost similar. In addition, the splitting tensile strength of the mortar sample with 100% ceramic aggregate was found to be 6% higher than the control sample. Thus, the homogenous ceramic tile waste can not only be used as sand replacement for normal application in mortar mix but also to enhance its hardened properties.